Prieto : Yorùbá Kingship in Colonial Cuba during the Age of Revolutions - Lovejoy, Henry B. (Book collections on Project MUSE., 2018)
"Centers on the life of Juan Nepomuceno Prieto (c. 1773-c. 1835), a member of the West African Yorùbá people enslaved and taken to Havana during the era of the Atlantic slave trade. ... Situating Prieto's story within the context of colonial Cuba, Henry B. Lovejoy illuminates the vast process by which thousands of Yorùbá speakers were forced into life-and-death struggles in a strange land"--